Implementation of Learning from Home as a Determinant of Social Development Problems for Preschool Children - Anggorowati, Lindra; Desty, Rani Tiara; Fauzi, Lukman; Yuliyana, Al Dina (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
Background: Learning From Home (BDR) policy since 2019 in controlling the transmission of Covid-19 in Indonesia is suspected to be able to cause children to be limited in getting stimulation for partnerships that should be built between parents, the community, and teachers. Forty percent of preschoolers are prone to social development problems. Researchers intend to know the implementation of BDR as a determinant of social development problems of preschool-age children (5-6 years). Methods: The study design of this research was analytically observational with a cross-sectional approach. The variables include the implementation of BDR, the mother’s education, the child’s gender, the child’s nutritional status, and the child’s social development. The instrument used is Denver II. The sampling method used a simple random sampling technique with as many as 113 samples. Data analysis was performed in a bivariable manner, with a chi-square test. Results: This study showed that the implementation of BDR was related to the problem of children’s social development (p-value = 0.012, OR = 1.639, 95% CI = 1.16-2.31). Mother’s education is related to children’s social development problems (p-value = 0.045, OR = 2.227, 95% CI = 1.93-5.3). Conclusion: Online BDR is a determinant of social development problems aged 5-6 years. The community and government need to anticipate problems that can occur through early detection of developments so that they can be overcome as early as possible. Parents should be involved in online BDR assistance to manage screen duration following safety standards for health.